Population Control and Family Life Education in South-South, Nigeria - Ushie, Doris Emmanuel; Edinyang, Sunday David; Igwe, Austin Robert; Ukam, Joy Anthony; Ejoh, Abigail Ojong (Mediterranean Journal of Social Sciences, 2020)
The purpose of this paper was to explore the importance of family life education in South-South Nigeria as regards population growth. An initiative has delved into the philosophical conceptions of schooling and the population in family life. It also presents an overview of the positive effects of education in family life. Today, population growth in South-South Nigeria presents many problems, including; poverty and unemployment. The paper accounts for ways in which family life education will play a significant role in improving the population's management. Finally, the article suggests that Growth and Development in adolescence is an integral component of family life education. Strengthened educational efforts should be undertaken in areas such as self-understanding, guardian relationships, jobs, obligations, feelings, stress management, dating, romance, maturity development, and enhancements to sexuality.